Pengaruh Current Ratio (CR), Return On Assets (ROA) dan Assets Growth (AG) terhadap Stuktur Modal (DER) pada PT Indofood Sukses Makmur Tbk periode 2014-2023 - Lestari, Siska; Supiyadi, Dedi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aimed to examine the effects of Current Ratio (CR), Return on Assets (ROA), and Assets Growth (AG) on the debt-to-equity ratio (DER) of PT Indofood Sukses Makmur Tbk from 2014 to 2023. The research employed descriptive and verification methods using a quantitative approach. Data was collected through documentation, utilizing secondary data from quarterly financial reports. The study used purposive sampling. Results of partial hypothesis testing (t-test) revealed that the Current Ratio (CR) had a significant positive effect on the debt-to-equity ratio (DER). In contrast, Return on Assets (ROA) and Assets Growth (AG) had positive but non-significant effects on DER. Simultaneous hypothesis testing (F-Test) showed that CR, ROA, and AG significantly impacted DER at PT Indofood Sukses Makmur Tbk, accounting for 50.9% of its variation. The remaining 49.1% was attributed to other factors not examined in this study